PENGARUH KEPUASAN KERJA DAN KOMITMENORGANISASIONAL TERHADAP KEINGINAN KELUAR KARYAWAN PADA MADE FERRY MOTOR DENPASAR - Wiranatha, Ida Bagus Agung; Surya, Ida Bagus Ketut (E-Jurnal Manajemen, 2016)
Job satisfaction and organizational commitment were important indicators to manager because it can maintain stable workforce. Employees with high level of commitment and satisfaction are believed not easy to leave their jobs. This study purposed to determine the effect of job satisfaction and organizational commitment on intention to quit in Made Ferry Motor Denpasar. This study used saturated sample where the entire population were sampled as many as 50 employees. Data analysis techniques used in this research is multiple linear regression. The findings of this study are: job satisfaction and organizational commitment has significant negative effect on intention to quit. The advices can be given included: Made Ferry Motor management should repairworkplace of employees to make them more comfortable; Made Ferry Motor management should make a better work atmosphere ; Made Ferry Motor management should gave more better salaries and allowances to meet the employee's needs.
Keywords: job satisfaction, organizational commitment, intention to quit